Pathological tumor response and its association with recurrence patterns and survival after neoadjuvant chemoradiotherapy and esophagectomy for esophageal squamous cell carcinoma: a tertiary care center experience from India - Feroz Khan; Suraj Surendran; Inian Samarasam; Myla Yacob; Negine Paul; Jansi Rani; Rajesh Isiah; Simon Pavamani; Balu Krishna Sasidharan; Manu Mathew (Korean Journal of Clinical Oncology, 2026)
Purpose: Neoadjuvant chemoradiotherapy (NACRT) followed by esophagectomy is a standard treatment for locally advanced esophageal squamous cell carcinoma (ESCC). Pathological response, assessed using tumor regression grade (TRG), is an established prognostic marker; however, evidence regarding its association with the pattern and timing of recurrence remains limited. This study evaluated recurrence patterns, timing of recurrence, and survival outcomes according to pathological tumor response following NACRT and esophagectomy for ESCC.Methods: We retrospectively analyzed 129 patients with ESCC who underwent NACRT followed by radical esophagectomy between January 2013 and June 2023. Pathological response was assessed according to the College of American Pathologists TRG system and categorized as TRG 0 (complete response), TRG 1 (near-complete response), TRG 2 (partial response), or TRG 3 (poor/no response). Recurrence patterns and timing, disease-free survival, and overall survival were compared across TRG categories.Results: Among 129 patients, 33 (25.6%) developed recurrence. Systemic recurrence was the most common pattern (16/33, 48.5%), followed by combined locoregional and systemic recurrence (9/33, 27.3%) and isolated locoregional recurrence (8/33, 24.2%). Patients with TRG 0 had the lowest proportion of isolated locoregional recurrence (16.7%), with systemic and combined recurrence accounting for 50.0% and 33.3%, respectively. In contrast, TRG 3 patients predominantly developed isolated locoregional recurrence (80.0%), with systemic recurrence occurring in 20.0%; all recurrences in this group occurred within 12 months, suggesting poorer local disease control.Conclusion: Poor pathological response was associated with earlier and predominantly locoregional recurrence, whereas favourable pathological response was associated with a greater proportion of systemic recurrence. These findings suggest that pathological tumor response may help inform postoperative risk stratification and guide individualized surveillance strategies in patients with ESCC.